Removal of Azo Dyes (Violet B and Violet 5R) from Aqueous Solution Using New Activated Carbon Developed from Orange Peel - Saeedeh Hashemian; Khaterah Salari; Hamila Salehifar; Zahra Atashi Yazdi (Journal of Chemistry)
Activated carbon developed from agricultural waste orange peel (COP) was prepared. COP was characterized using Fourier infrared spectroscopy (FTIR), X-ray powder diffraction (XRD), scanning electron microscopy (SEM), and BET. COP has surface area and mean pore diameter of 225.6 m2 g−1 and 22.40 nm, respectively. The removal of violet B (VB) and violet 5R (V5R) from aqueous solutions by COP was investigated. The effect of operational parameters such as contact time, pH, initial dye concentration, and adsorbent dosage on the adsorption of dyes was investigated. Maximum dye was removed within 30 min of contact time at pH > 7. Two common models, the Langmuir and Freundlich isotherms, were used to investigate the interaction of dye and COPs. The isotherm evaluations revealed that the Langmuir model provides better fit to the experimental data than the Freundlich model. The adsorption of VB and V5R onto COP was followed by pseudo-second-order kinetic model with a good correlation (R2>0.99). Activation energies 5.47 and 29.7 KJ mol−1 were determined for violet B and violet 5R, respectively. The rate of adsorption of violet 5R was faster than that of violet B (kV5R>kVB). The prepared COP could thus be used as promising adsorbent for removal of organic dyes, especially azo dye, from polluted water. The solid COP could be conveniently regenerated after adsorption.